(untitled) (Al-Qamar, 2019)
The discussions on the issue of the authenticity of Ḥadtīh literature may be traced back to centuries. Both Muslims and non-Muslims scholars have worked in the field. Many Western scholars deny the Ḥadtīh literature as an authentic source of history. This paper intends to elucidate the broad-spectrum guiding principles for substantiating and authenticating the historical sources, then to explain the principles of criticism used in validating and corroborating Ahādīth. It, after presenting a comparative study of Muslim and Western critical methodologies, indorsed the idea of considering Ḥadtīh as an authentic source of history.